Preparation method and application of carbon fluoride positive pole piece based on recycled graphite

By removing metal foils, washing and fluorinating the graphite material in the waste lithium battery, high energy density fluorinated carbon positive electrode material is prepared, which solves the problem of difficult graphite recycling and achieves efficient resource reuse and excellent battery performance.

CN119674298APending Publication Date: 2025-03-21XIAMEN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411826730.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The graphite materials in existing lithium-ion batteries are difficult to recover, dust pollution is serious, and the artificial graphite process is cumbersome and energy-consuming, so it is impossible to effectively utilize the graphite resources in waste batteries.

Method used

By removing the metal foil sheets in the used lithium battery, washing and fluorinating the graphite negative electrode sheets, a high-energy density fluorinated carbon positive electrode material was prepared and applied to the positive electrode of the lithium battery.

Benefits of technology

The efficient recycling and reuse of waste lithium battery graphite is achieved, and the prepared carbon fluorinated cathode material has higher energy density and excellent rate performance, and reduces the preparation energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674298A_ABST
    Figure CN119674298A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a carbon fluoride positive pole piece based on recycled graphite, and the method comprises the following steps: adding a carbon fluoride positive pole material, a conductive agent and a binder into a solvent, and carrying out ball milling to obtain slurry; and coating a carbon-coated aluminum foil with the slurry, and then carrying out vacuum drying to obtain the carbon fluoride positive pole piece. The method comprises the following steps: recovering graphite in a waste lithium battery to obtain recovered graphite, and then fluorinating the recovered graphite to obtain the carbon fluoride positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials, and relates to a method for preparing a carbon fluoride positive electrode sheet based on recycled graphite and its application. Background Art

[0002] With the rapid development of military equipment and aerospace, the energy storage field urgently needs advanced cathode materials with high energy density, high power density and excellent safety. Carbon fluoride, also known as graphite fluoride, has a chemical formula of CF x , x can generally vary between 0-1.3. Carbon fluoride is the conversion cathode material with the highest energy density in primary batteries. Lithium / carbon fluoride (Li / CF x The superiority of Li / CF batteries lies in their outstanding theoretical energy density of 2180Wh / kg, which exceeds other primary lithium batteries, including lithium / manganese dioxide (Li / MnO2) batteries, lithium / thionyl chloride (Li / SOCl2) batteries, and lithium / sulfur dioxide (Li / SO2) batteries. x Batteries are used in a wide variety of industries, including military, aerospace, and medical applications.

[0003] At present, there are a huge number of retired lithium-ion batteries. Graphite, as the preferred negative electrode material for lithium-ion batteries, has a large market share. Direct discharge of graphite from waste batteries is prone to dust pollution. After graphite dust enters the human body, it will damage the respiratory system and cause respiratory dysfunction. In addition, the process of artificial graphite is cumbersome, energy-intensive, and time-consuming. Therefore, recycling graphite from waste batteries is conducive to the sustainable use of resources, which can not only reduce energy and material consumption, but also conform to the concept of green, low-carbon, and high-quality development. Summary of the invention

[0004] The present disclosure provides a method for preparing a carbon fluoride positive electrode sheet based on recycled graphite and its application, which can effectively solve the above problems.

[0005] The present disclosure is implemented as follows:

[0006] In one aspect, the present disclosure provides a method for preparing a fluorinated carbon cathode material based on recycled graphite, comprising:

[0007] Removing metal foil from graphite negative electrode sheets in waste lithium batteries to separate active materials, wherein the waste lithium batteries are lithium batteries having a battery capacity no greater than 80% of the original battery capacity;

[0008] Washing the active material with deionized water to obtain recovered graphite;

[0009] The recovered graphite is fluorinated to obtain the material.

[0010] In another aspect, the present disclosure provides a method for preparing a fluorinated carbon positive electrode sheet, comprising:

[0011] The carbon fluoride positive electrode material, conductive agent and binder prepared by the above method are added into a solvent and ball-milled to obtain a slurry;

[0012] The slurry is coated on a carbon-coated aluminum foil and then vacuum dried to obtain the carbon fluoride positive electrode sheet.

[0013] On the other hand, the present disclosure provides an application of a carbon fluoride positive electrode sheet prepared by the above method in a lithium battery.

[0014] The beneficial effects of the present disclosure are:

[0015] The present disclosure provides a method for preparing a fluorinated carbon positive electrode material, wherein the graphite in waste lithium batteries is recovered to obtain recycled graphite, and then the recycled graphite is fluorinated to obtain a fluorinated carbon positive electrode material, which has a lower degree of graphitization and a higher degree of fluorination than fluorinated commercial graphite, and thus has a higher energy density, and can be applied to lithium battery positive electrodes to obtain better rate performance.

[0016] Furthermore, in the preparation method of the fluorinated carbon positive electrode material, the energy density of the fluorinated carbon positive electrode material obtained by lowering the fluorination temperature of the recycled graphite to 700°C and the rate performance applied to the positive electrode of a lithium battery are both better than those of the fluorinated commercial graphite prepared at 750°C. Therefore, the energy consumption required for preparation can be reduced by lowering the fluorination temperature.

[0017] Furthermore, the lithium battery made using the carbon fluoride positive electrode material can maintain an excellent discharge specific capacity of 801 mAh / g at a current density of 2C, and still has a capacity retention rate of 91.2% at a high current density of 5C. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 TEM image of the recycled graphite obtained in the examples of the present disclosure.

[0020] Figure 2 The overall SEM images of the recycled graphite and commercial graphite prepared in the examples of the present disclosure are shown in FIG.

[0021] Figure 3The single particle SEM images of the recycled graphite and commercial graphite prepared in the examples of the present disclosure are shown in FIG.

[0022] Figure 4 This is a cycle performance diagram of the recycled graphite positive electrode prepared in the embodiment of the present disclosure.

[0023] Figure 5 The overall SEM images of 750°C-commercial fluorinated graphite, 700°C-recycled fluorinated graphite, and 750°C-recycled fluorinated graphite prepared in the examples of the present disclosure are shown.

[0024] Figure 6 The single particle SEM images of 750°C-commercial fluorinated graphite, 700°C-recycled fluorinated graphite, and 750°C-recycled fluorinated graphite prepared in the examples of the present disclosure are shown.

[0025] Figure 7 These are SEM EDS images of 750°C-commercial fluorinated graphite, 700°C-recycled fluorinated graphite, and 750°C-recycled fluorinated graphite prepared in the examples of the present disclosure.

[0026] Figure 8 These are the XRD patterns of 750°C-commercial fluorinated graphite, 700°C-recycled fluorinated graphite, and 750°C-recycled fluorinated graphite prepared in the examples of the present disclosure.

[0027] Fig. 9 This is a rate diagram of a 750°C commercial graphite fluoride positive electrode prepared in an example of the present disclosure.

[0028] Fig.10 This is a rate diagram of the 750°C-recovered graphite fluoride positive electrode prepared in the examples of the present disclosure.

[0029] Fig.11 This is a rate diagram of the 700°C-recovered graphite fluoride positive electrode prepared in the examples of the present disclosure. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present disclosure clearer, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present disclosure. Therefore, the following detailed description of the embodiments of the present disclosure provided in the drawings is not intended to limit the scope of the present disclosure for protection, but merely represents the selected embodiments of the present disclosure. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present disclosure.

[0031] The present disclosure provides a method for preparing a fluorinated carbon cathode material, comprising:

[0032] Removing metal foil from graphite negative electrode sheets in waste lithium batteries to separate active materials, wherein the waste lithium batteries are lithium batteries having a battery capacity no greater than 80% of the original battery capacity;

[0033] Washing the active material with deionized water to obtain recovered graphite;

[0034] The recovered graphite is fluorinated to obtain the material.

[0035] In the method, the sources of graphite in waste lithium batteries are abundant, the recovery process is simple, and the graphite in waste lithium batteries can be recovered and reused.

[0036] The fluorinated product of graphite, carbon fluoride, has good chemical stability and electronic insulation. The covalent CF bond gives CF x Good chemical stability and electronic insulation, and the semi-ionic CF bond does not destroy the sp 2 The hybrid structure maintains the conjugated structure of the initial carbonaceous material and has good electronic conductivity.

[0037] Carbon fluoride has a significant effect on improving the discharge capacity of batteries.

[0038] The recycled graphite is used as the material of the negative electrode plate of the waste lithium battery. During the use of the lithium battery, lithium ions are repeatedly embedded / released, resulting in a larger interlayer spacing. At the same time, the particle surface is also damaged to a certain extent, forming defects, and the integrity is not as good as commercial graphite.

[0039] The surface of the recycled graphite is damaged due to the co-insertion of solvated lithium ions during the initial formation of the solid electrolyte interface (SEI) and the cavitation effect of the reaction of lithium with water to form hydrogen.

[0040] The waste lithium battery is defined as a lithium battery with a battery capacity not greater than 80% of the original battery capacity. This is based on the fact that during the process of battery capacity decay of the waste lithium battery, the recycled graphite in its negative electrode plate is repeatedly embedded / released by lithium ions, resulting in an increase in the interlayer spacing and damage to the particle surface. The degree of fluorination of the carbon fluoride obtained by subsequent fluorination reaction of the recycled graphite meets the requirement of improving the energy density of the battery when the carbon fluoride is applied to the positive electrode of the lithium battery.

[0041] Therefore, when the recycled graphite is subjected to high-temperature fluorination, due to the large interlayer spacing, more fluorine can be inserted between the graphite layers, and the defects on the particle surface can promote the occurrence of the fluorination reaction. When the recycled graphite is subjected to the fluorination reaction, the fluorine participation process is higher than that of commercial graphite, thereby obtaining a higher degree of fluorination and a lower degree of graphitization. When it is applied to the positive electrode of a lithium battery, it can make the battery have a higher energy density.

[0042] In some embodiments, the metal foil is removed from the graphite negative electrode plate in the waste lithium battery to separate the active material. The specific steps include: immersing the electrode plate in deionized water for 10 minutes, then clamping it with tweezers and gently shaking it to completely separate and remove the metal foil to obtain the black active material.

[0043] In some embodiments, the active material is washed with deionized water, and the specific steps include: adding the black active material into deionized water, stirring with a magnetic stirrer for 10 minutes and then filtering, and repeating three times.

[0044] Since the conductive agent and binder in commercial lithium-ion batteries account for a small proportion (approximately less than 5%) and most of the binders used are water-based, they will dissolve in deionized water during rinsing and be removed during filtration.

[0045] In some embodiments, the recycled graphite is fluorinated to obtain the material, comprising:

[0046] The recovered graphite is vacuum dried and then placed in a nickel reactor. A mixed gas of nitrogen and fluorine is introduced into the nickel reactor to carry out a fluorination reaction at a temperature of 700-750° C. to obtain the material, wherein the volume ratio of nitrogen to fluorine is 1:2.8-3.2.

[0047] The fluorination method is simple to operate and can fully fluorinate the carbon atoms in the recovered graphite, so that the fluorination degree of the prepared fluorinated carbon material reaches the expected level.

[0048] In some embodiments, the pressure of the mixed gas of nitrogen and fluorine is 0.24-0.26 MPa.

[0049] In some embodiments, the fluorination reaction is performed at a temperature of 700°C.

[0050] The higher the fluorination temperature, the greater the fluorine-to-carbon ratio of the product. The conventional fluorination temperature of commercial graphite is 750°C. The recycled graphite can be fluorinated at 700°C, and the fluorine-to-carbon ratio of the obtained product is greater than that of the commercial fluorinated graphite obtained by fluorination at 750°C. Therefore, the fluorination of the recycled graphite at 700°C can reduce the energy consumption required for preparation and obtain a material with excellent performance.

[0051] In some embodiments, the molar ratio of the recycled graphite to the fluorine gas is 1:1.

[0052] Theoretically, when x=1, carbon fluoride (CF x ) positive electrode achieves the highest specific capacity (865mAh / g) and energy density (2180Wh / kg). Therefore, the fluorination is carried out with an atomic ratio of C and F of 1:1, so that the F / C ratio of the fluorinated product is about 1.

[0053] Excessive use of fluorine gas: As the F content increases, more covalent CF bonds will appear in the fluorination product carbon fluoride, which will reduce the conductivity of the carbon fluoride positive electrode, resulting in a significant decrease in its electrochemical performance, or even failure to release capacity.

[0054] Too much recycled graphite: The theoretical specific capacity of the battery is only related to the F / C ratio x. The more carbon content, the lower the degree of fluorination, and it becomes low-fluorinated graphite CF. (0.5-0.99) , the maximum capacity cannot be reached.

[0055] In some embodiments, the electrolyte of the waste lithium battery is a fluorine-containing electrolyte.

[0056] During the use of lithium batteries, due to the decomposition of fluorine-containing electrolytes, an appropriate amount of fluoride (lithium fluoride LiF, fluorine-containing functional groups, etc.) will remain on the surface of the graphite negative electrode. Therefore, there will be residual fluoride on the surface of the recycled graphite.

[0057] The fluorides such as LiF have the advantages of lower diffusion energy barrier, wider electrochemical stability window and lower electronic conductivity / ionic conductivity ratio, which have a positive effect on the inhibition of lithium dendrites. In addition, these residual fluorides contribute to the reversible insertion / extraction of lithium ions, so that the recycled graphite obtains a larger interlayer spacing. After fluorination, the fluorination degree of the product is further improved.

[0058] The present disclosure provides a method for preparing a carbon fluoride positive electrode sheet, comprising:

[0059] The carbon fluoride positive electrode material, conductive agent and binder prepared by the above method are added into a solvent and ball-milled to obtain a slurry;

[0060] The slurry is coated on a carbon-coated aluminum foil and then vacuum dried to obtain the carbon fluoride positive electrode sheet.

[0061] In some embodiments, the mass ratio of the carbon fluoride positive electrode material to the carbon-coated aluminum foil is 0.48-0.54:1.

[0062] The loading of appropriate amount of active materials can effectively improve the battery energy density while reducing the cost.

[0063] In some embodiments, the mass ratio of the carbon fluoride positive electrode material, the conductive agent, and the binder is 7.8-8.2:0.95-1.05:1.

[0064] By optimizing the mass ratio of each component in the slurry, the energy density, power density and cycle stability of the battery can be improved.

[0065] In some embodiments, the ball milling speed is 400 r / s, and the ball milling time is not less than 4 hours.

[0066] The purpose of ball milling is to make the slurry mix more evenly and the thickness of the scraped electrode more uniform. If the ball milling time is less than 4 hours, the slurry will be unevenly mixed.

[0067] The disclosed embodiments provide the use of the carbon fluoride positive electrode sheet prepared by the above method in a lithium battery.

[0068] Example 1

[0069] Preparation of carbon fluoride positive electrode material:

[0070] The specific steps include:

[0071] Step 1: Soak the graphite negative electrode obtained from the waste soft-pack lithium battery in deionized water. The copper foil will be completely separated from the active material during the soaking process. After the copper foil is taken out, the remaining black active material is washed three times and filtered, and then vacuum dried at 80°C in a vacuum drying oven overnight to obtain recycled graphite.

[0072] Step 2: Place the recovered graphite obtained in step 1 in a nickel reactor, introduce a mixed gas of nitrogen and fluorine into the nickel reactor, and perform a fluorination reaction at a temperature of 750° C. for 24 hours to obtain carbon fluoride CF x Positive electrode material. The molar ratio of the recycled graphite to the fluorine gas is 1:1, and the volume ratio of the nitrogen gas to the fluorine gas is 1:3.

[0073] The CF prepared in Example 1 x The positive electrode material is named 750℃-recycled graphite fluoride.

[0074] Example 2

[0075] The recovered graphite obtained in step 1 is placed in a nickel reactor, a mixed gas of nitrogen and fluorine is introduced into the nickel reactor, and a fluorination reaction is carried out at a temperature of 700°C for 24 hours to obtain carbon fluoride CF x Positive electrode material. The molar ratio of the recycled graphite to the fluorine gas is 1:1, and the volume ratio of the nitrogen gas to the fluorine gas is 1:3.

[0076] The CF prepared in Example 2x The positive electrode material is named 700℃-recycled graphite fluoride.

[0077] Example 3

[0078] Commercial graphite is placed in a nickel reactor, a mixed gas of nitrogen and fluorine is introduced into the nickel reactor, and a fluorination reaction is carried out at a temperature of 750°C for 24 hours to obtain carbon fluoride CF x Positive electrode material. The molar ratio of the recycled graphite to the fluorine gas is 1:1, and the volume ratio of the nitrogen gas to the fluorine gas is 1:3.

[0079] Among them, commercial graphite was purchased from Zhejiang Chaowei Chuangyuan Industrial Co., Ltd.

[0080] The CF prepared in Example 3 x The positive electrode material is named 750℃-commercial graphite fluoride.

[0081] Test Example 1

[0082] The crystal plane distance of the recovered graphite obtained in step 1 of Example 1 was characterized using a high-resolution transmission electron microscope (HRTEM). The TEM characterization results are as follows: Figure 1 shown.

[0083] Can be obtained from Figure 1 The recovered graphite was observed to have a basic graphite layer structure with an average interlayer spacing of 0.342 nm, which is slightly larger than commercial graphite (0.335 nm). Therefore, it can be concluded that the interlayer spacing of the recovered graphite is larger.

[0084] The surface morphologies of the recovered graphite obtained in step 1 of Example 1 and the commercial graphite in Example 3 were characterized using a scanning electron microscope (SEM). The SEM characterization results are shown in FIG. Figure 2 and Figure 3 shown.

[0085] Can be obtained from Figure 2 It is observed that the commercial graphite particle size is relatively uniform. The size of the recycled graphite particles is inconsistent, which is attributed to the different degrees of destruction of the recycled graphite particles in the chemical reaction, so they present different sizes, but the overall size of the recycled graphite is smaller than that of the commercial graphite.

[0086] The average length of the recycled graphite particles is 21.32 μm and the average width is 14.60 μm. The average length of the commercial graphite particles is 29.80 μm and the average width is 17.18 μm.

[0087] Can be obtained from Figure 3 It was observed that no impurities appeared in the SEM image of the recovered graphite, which suggests that the conductive carbon, binder and recovered graphite were separated after filtration.

[0088] It should be pointed out that the above analysis mentioned that commercial graphite particles are relatively complete, while recycled graphite particles have some defects. This defect refers to the defects in the crystal structure (atomic size, the order of magnitude of atomic diameter is about 10 -10 m), which is a microscopic structure. The size of the SEM image is micrometer-level (10 -6 m), which is more macroscopic in comparison, so no obvious defects can be seen in the SEM image.

[0089] therefore, Figure 2 and Figure 3 It shows more that compared with commercial graphite particles, the structure of recycled graphite particles is also intact (indicates that there is not much damage and it can still be used normally), but the particle size has become smaller.

[0090] According to the mass ratio of 9:1, the recycled graphite and polyvinylidene fluoride (PVDF) were added with N-methylpyrrolidone (NMP) as a solvent to prepare a graphite negative electrode, and the half-cell was assembled for cycle performance test. The battery was charged and discharged at a current density of 0.1C in the working range of 0.005-2V. The specific steps include: constant current discharge to 0.005V, stand for 5 minutes, constant current charge to 2V, stand for 5 minutes, and repeat the above steps for circulation.

[0091] The test results are as follows Figure 4 shown.

[0092] from Figure 4 It can be seen that the first discharge specific capacity of the prepared half-cell is 361.4 mAh / g, and the first charge specific capacity is 304.4 mAh / g, indicating that the recycled graphite can be reused as electrode material.

[0093] Test Example 2

[0094] The CF prepared in Examples 1-3 were respectively stained with SEM. x The surface morphology of the positive electrode material was characterized, and the SEM characterization results were as follows Figure 5 and Figure 6 shown.

[0095] The left picture shows commercial fluorinated graphite at 750℃, which has a smooth surface and high particle integrity. The picture shows recycled fluorinated graphite at 700℃, which has a rough surface and is covered with small debris. The right picture shows recycled fluorinated graphite at 750℃, which has a higher degree of surface damage and defects than the first two, with larger debris.

[0096] Depend on Figure 6 It can be seen that the recycled graphite can produce more defects after fluorination, for lithium / carbon fluoride (Li / CF x) batteries, the rich defects provide more reactive fluorine-containing active centers, introduce more semi-ionic CF bonds, and increase the F / C ratio. Increasing the fluorination degree of fluorocarbon materials is the key to increasing the Li / CF ratio. x The most efficient way to increase battery energy density.

[0097] CF x The presence of defects in the positive electrode material and the expansion of the interlayer spacing can significantly improve its reaction activity and further provide more fluorination sites. At the same time, the synergistic effect of fluorine doping and defects can further enhance the electrochemical performance of the material.

[0098] Furthermore, the carbon-fluorine ratios of the three materials were detected using SEM energy dispersive X-ray spectroscopy (EDS). The EDS characterization results are as follows: Figure 7 shown.

[0099] 750℃-The F content of commercial graphite fluoride is lower than the C content.

[0100] The F / C ratios of 750℃-recovered fluorinated graphite and 700℃-recovered fluorinated graphite are significantly higher than that of 750℃-commercial fluorinated graphite. Compared with the two, the higher the fluorination temperature, the greater the F / C ratio of the material. The F / C ratio of 700℃-recovered fluorinated graphite is close to 1, and the F / C ratio of 750℃-recovered fluorinated graphite is greater than 1.

[0101] The crystal structures of the three materials were characterized by X-ray diffraction (XRD). Figure 8 shown.

[0102] The XRD spectrum of the fluorinated carbon material reveals a diffraction peak near 2θ = 15.1°, corresponding to the CF with a higher degree of fluorination. x The diffraction peak at 2θ = 40.4° is attributed to the in-plane CF x The (100) crystal plane of the network. The diffraction peak at 2θ=27.0° can be attributed to the (002) crystal plane. The peak intensity of the (002) peak shows that the degree of fluorination of the recycled graphite fluoride is higher than that of the commercial graphite fluoride, and the degree of graphitization is lower.

[0103] Compared with commercial graphite, recycled graphite has a larger interlayer spacing after repeated insertion / extraction of lithium ions, and its surface is also damaged to a certain extent, making it less complete than commercial graphite. During the fluorination process, fluorine atoms are inserted between graphite layers, and the fluorine atoms form covalent bonds with the 2Pz orbital electrons of carbon atoms, increasing the distance between carbon atoms in the layer to The layers bend, thus losing the conductivity of graphite and becoming an insulator. At the same time, due to the electronegativity of fluorine atoms, the distance between carbon atoms in the layers is Stretch to This further destroys the integrity of the material's crystal structure.

[0104] Since the fluorine involved in the recycled graphite is higher than that in commercial graphite during the fluorination process, its graphitization degree is lower.

[0105] Example 5

[0106] Preparation of carbon fluoride primary battery:

[0107] Step 1, according to the mass ratio of 8:1:1, take 0.32 mg of active material, 0.04 mg of conductive carbon black (Super P) and 0.04 mg of polyvinylidene fluoride (PVDF), add 20 drops of N-methylpyrrolidone (NMP) as solvent, and ball mill in an agate ball mill for 4 h at a rotation speed of 400 r / s to obtain a slurry.

[0108] The added PVDF was prepared into a solution with a mass fraction of 5%. Specifically, 1 gram of PVDF powder and 19 grams of NMP were magnetically stirred for 24 hours to prepare a solution. Therefore, the mass of the added PVDF solution was 0.8 mg. The NMP solvent will evaporate in the subsequent vacuum drying process.

[0109] The active substances are selected from CF prepared in Examples 1-3. x The prepared battery samples are named 750℃-commercial graphite fluoride battery, 750℃-recycled graphite fluoride battery and 700℃-recycled graphite fluoride battery respectively.

[0110] Step 2: coat the slurry on the carbon-coated aluminum foil with a scraper height of 120 μm, and then place the coated carbon-coated aluminum foil in a vacuum drying oven at 120° C. for 12 hours.

[0111] The height of the scraper is set to obtain a positive electrode sheet with a loading of 1.8-2.0 mg (the mass of active material after deducting the carbon-coated aluminum foil, conductive agent and binder).

[0112] Step 3: Cut the dried carbon-coated aluminum foil into small discs with a diameter of 12 mm and weigh them. The mass of the carbon-coated aluminum foil is about 3.7 mg, and the mass of the carbon fluoride material is 1.8 mg to 2.0 mg.

[0113] Step 4, place the positive electrode sheet into a glove box, use a lithium sheet as the negative electrode, the electrolyte is a 1M lithium hexafluorophosphate (LiPF6) solution, and the solvent is a solution of propylene carbonate (PC) and 1,2-dimethoxyethane mixed in a mass ratio of 1:1:1.

[0114] The half-cell was assembled according to a conventional assembly method, and the cell was kept under a pressure of 1000 psi on a tablet press for 5 seconds to obtain a carbon fluoride primary battery.

[0115] The purpose of pressing is to make the positive and negative poles of the battery tightly combined together to avoid leakage of electrolyte during testing, and to prevent air from entering and oxidizing the electrolyte and lithium sheets, causing some unnecessary errors and leading to experimental failure.

[0116] Test Example 2

[0117] At a current density of 0.1-5C, 1.5-3.5V (vs. Li / Li + ) voltage range, the three battery samples were tested for rate performance. The test results are as follows Figure 9-11 shown.

[0118] By comparison, it was found that as the discharge current increased, the discharge voltage platform and specific capacity both decreased.

[0119] Fig. 9 and Fig.11 The discharge capacity at 0.1C is 830mAh / g, and as the current density increases, the 700℃-recycled graphite fluoride battery shows excellent rate performance. At a current density of 2C, the 700℃-recycled graphite fluoride battery can maintain an excellent discharge capacity of 801mAh / g, and at a high current of 5C, it has a capacity retention rate of 91.2%.

[0120] The above analysis shows that even if the fluorination temperature is lowered, the battery made from the fluorination product of recycled graphite still has better performance than commercial graphite.

[0121] Fig.10 The 750℃-recovered graphite fluoride battery can maintain an excellent discharge specific capacity of 812mAh / g at a current density of 3C, and has a capacity retention rate of 93.7% at a high current of 5C.

[0122] By increasing the temperature at which the recycled graphite is fluorinated, the rate performance, discharge specific capacity and capacity retention rate of the prepared carbon fluoride primary battery can be improved.

[0123] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.

Claims

1. A method for preparing a fluorinated carbon cathode material based on recycled graphite, characterized in that: include: Removing metal foil from graphite negative electrode sheets in waste lithium batteries to separate active materials, wherein the waste lithium batteries are lithium batteries having a battery capacity no greater than 80% of the original battery capacity; Washing the active material with deionized water to obtain recovered graphite; The recovered graphite is fluorinated to obtain the material.

2. The method according to claim 1, characterized in that The recovered graphite is fluorinated to obtain the material, comprising: The recovered graphite is vacuum dried and then placed in a nickel reactor. A mixed gas of nitrogen and fluorine is introduced into the nickel reactor to carry out a fluorination reaction at a temperature of 700-750° C. to obtain the material, wherein the volume ratio of nitrogen to fluorine is 1:2.8-3.

2.

3. The method according to claim 2, characterized in that The fluorination reaction was carried out at a temperature of 700°C.

4. The method according to claim 2, characterized in that The molar ratio of the recovered graphite to the fluorine gas is 1:

1.

5. The method according to claim 1, characterized in that The electrolyte of the waste lithium battery is a fluorine-containing electrolyte.

6. A method for preparing a fluorinated carbon positive electrode sheet, characterized in that: include: Adding the carbon fluoride positive electrode material, conductive agent and binder prepared by the method according to any one of claims 1 to 5 into a solvent, and ball milling to obtain a slurry; The slurry is coated on a carbon-coated aluminum foil and then vacuum dried to obtain the carbon fluoride positive electrode sheet.

7. The method according to claim 6, characterized in that The mass ratio of the carbon fluoride positive electrode material to the carbon-coated aluminum foil is 0.48-0.54:

1.

8. The method according to claim 6, characterized in that The mass ratio of the carbon fluoride positive electrode material, the conductive agent and the binder is 7.8-8.2:0.95-1.05:

1.

9. The method according to claim 6, characterized in that The ball milling speed is 400r / s, and the ball milling time is not less than 4h.

10. Use of the carbon fluoride positive electrode sheet prepared by the method according to any one of claims 6 to 9 in lithium batteries.